2022
DOI: 10.3390/su14159100
|View full text |Cite
|
Sign up to set email alerts
|

Compressive and Shear Strengths of Coir Fibre Reinforced Activated Carbon Stabilised Lateritic Soil

Abstract: Constructing structures on lateritic soil is challenging in geotechnical engineering due to the various physical and geotechnical characteristics. Many studies investigated different stabiliser materials to strengthen the geotechnical parameters of lateritic soil. This study used activated carbon and coir fibre (ACF) to stabilise lateritic soils as an environmentally friendly binder. Experiments including the unconfined compressive strength (UCS) test and the direct shear test (DST) are performed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Furthermore, the addition of fiberglass was ineffective to deduce the volumetric strain of fiber-reinforced sulfate-rich dispersive soil. Tamassoki et al 22 stated that 3% content of activated carbon and coir fiber can significantly improved the compressive strength, while 2% content can remarkably enhanced the shear strength of lateritic soil. Soleimani-Fard et al 23 revealed that discrete distributed fibers can significantly improved the shear strength, compressive, and hydraulic conductivity of fiber-reinforced fine-grained soil.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of fiberglass was ineffective to deduce the volumetric strain of fiber-reinforced sulfate-rich dispersive soil. Tamassoki et al 22 stated that 3% content of activated carbon and coir fiber can significantly improved the compressive strength, while 2% content can remarkably enhanced the shear strength of lateritic soil. Soleimani-Fard et al 23 revealed that discrete distributed fibers can significantly improved the shear strength, compressive, and hydraulic conductivity of fiber-reinforced fine-grained soil.…”
Section: Introductionmentioning
confidence: 99%
“…The cement hydration and pozzolanic reactions produce calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH), leading to strength gains in calcium-based stabilized geomaterials [ 100 , 101 ], particularly cement-stabilized composites [ 102 , 103 ]. A previous study’s findings showed that cement hydration products fully adhere to the surface of carbon nanomaterials [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a reinforcement, synthetic and natural fibre increases tensile strength, improves stability (Tamassoki et al, 2022a) and reduces soil lateral deformation/settlement (He et al, 2021). Furthermore, adding fibre to lime/cement-stabilised soil can reduce the brittleness of treated soil (Hamidi & Hooresfand, 2013).…”
Section: Introductionmentioning
confidence: 99%